Digitalisasi UMKM dan Inovasi Pembelajaran Desa Baharen - Riezky Bagus Prawira Darwadi; Mara Hamdan Tambunan; Bunga Amirah; Rendy Prayuda; Siti Aisyah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The rapid development of digital technology requires greater adaptive capacity in both the economic and educational sectors, including in rural areas. However, limited digital literacy and the continued use of conventional learning methods remain common challenges. This activity aims to enhance the competitiveness of micro, small, and medium enterprises (MSMEs) as well as the quality of primary education in Baharen Village, Sidamanik District, through the implementation of a Community Service Program (Kuliah Kerja Nyata/KKN). A descriptive qualitative approach with a participatory model was employed, actively involving MSME actors, teachers, and students throughout all stages of the program. The activities included assistance in the digitalization of the MSME Gerai Mumtazah through Google Maps registration and the implementation of the QRIS cashless payment system, as well as the application of interactive learning methods based on joyful learning at the Baharen Village State Elementary School. The results indicate an increase in students’ learning motivation and classroom participation, along with improved accessibility and transaction efficiency for the MSME partner. These findings suggest that community-based participatory service activities can make a tangible contribution to strengthening the local economy and improving the quality of education in rural areas.